Late Quaternary Morphotectonics of the Hetauda Dun, Nepal Sub Himalaya - Kimura, Kazuo (Journal of Nepal Geological Society, 1995)
The Hetauda Dun, a tectonic valley in the Sub-Himalaya, is separated from the Gangetic plain by the Outer Churia Range. This range was upheaved in the late Pleistocene giving rise to the Dun valley. The tectonics of the area are characterised by fault propagation tectonics caused by the migration of the active front from the Central ChuriaThrust (CCT) to the Himalayan Front Thrust (HFT). After the closure of the Dun, another active anticlinal structure related to thrust imbrication has developed in the central part of the valley on the hanging wall of the CCT. The crustal movement continues under the same stress field of the prior tectonic phase, characterised by the shortening of the Sub-Himalaya along the NNW-SSE direction.